Réponses

  • Utilisateur Brainly
2013-11-09T17:29:35+01:00
Factoriser :
E=4x² - 1
=(2x-1)(2x+1)

F= (2x+1)(x+7) + (x-1)(x+7)
=(x+7)(3x)

G=(2x+1)²-(3x-1)(2x+1)
=(2x+1)(-x+2)

H=2x³ + 5x²
=x²(2x+5)

I= (x-1)²-(2x-3)²

=(3x-4)(-x+2)

J= 4x² -12x +9
=(2x-3)²

K= (4x+3)(x-1)+4x+3
=(4x+3)(x)

L= 5-x+(x-5)(2x+1)

=(5-x)(-2x)
Meilleure réponse !
2013-11-09T17:34:33+01:00
E=4x² - 1 
=(2x+1)(2x-1)


F= (2x+1)(x+7) + (x-1)(x+7)
=(x+7)(2x+1+x-1)
=3x(x+7)

G=(2x+1)²-(3x-1)(2x+1)
=(2x+1)(2x+1)-(2x+1)(3x-1)
=(2x+1)(2x+1-3x+1)
=-x(2x+1)
=x(-2x-1)

H=2x³ + 5x²
=x²(2x+5)

I= (x-1)²-(2x-3)²
=(x-1-2x+3)(x-1+2x-3)
=(-x+2)(3x-4)

J= 4x² -12x +9
=(2x-3)²

K= (4x+3)(x-1)+4x+3
=
(4x+3)(x-1)+(4x+3)
=(4x+3)(x-1+1)
=x(4x+3)

L= 5-x+(x-5)(2x+1)
=-(x-5)+(x-5)(2x+1)
=(x-5)(2x+1-1)
=2x(x-5)